Failure Rate of Pediatric Dental Treatment under General Anesthesia - Effat Khodadadi; Mehrnaz Mohammadpour; Saeed Reza Motamedian; Farnaz Kouhestani (MDPI AG, 2018)
Aim: To assess the failure rates of various pediatric dental treatments performed under general anesthesia (GA) after six months to five years of follow-up. Design: This multicenter retrospective cohort study was performed on patients treated by five pedodontists in two private hospitals located in northern Iran during 2010–2013 and comprised 155 patients. The patients were recalled and clinically examined. During the clinical examination of the primary teeth, oral hygiene, dmft index, and failure of previous treatments was evaluated. The data were analyzed using the Chi square and regression analyses with a significance level of 0.05. Results: 114 patients (74 males and 40 females, mean age: 37.17 ± 10.75 months) with 1155 primary teeth treated under GA participated in the follow-up. The overall failure rate was 6.59%. The failure rates of pulpectomy, pulopotomy, fissure sealant, stainless steel crown (SSC), amalgam, and composite fillings were 2.90%, 3.03%, 4.83%, 5.26%, 5.33%, and 9.63%, respectively. Among the confounding factors, only gender had a significant effect on the anterior composite failure rate (p = 0.029) and age had a significant effect on the failure rate of fissure sealant therapy (p = 0.015) and SSC (p = 0.018). Conclusion: The overall rate of treatment failure in pediatric patients, treated under GA, was 6.59%.